RENAL SYMPTOM: VARIANTS OF INTERPRETATION - T. V. Kulichenko; M. A. Lazareva; A. V. Nikitin; H. V. Zhurkova (Педиатрическая фармакология, 2014)
Clinical task.Parents of a 3.5-year-old girl consulted a doctor due to the girl’s unusual urine color.The day before the girl had been complaining of pains in the lower abdomen. The girl urinated at night; in the morning the father discovered that the urine was bright crimson.